PERAN MOTIVASI SEBAGAI MEDIATOR DIMENSI KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. NETINDO SOLUTION YOGYAKARTA - Maya NunghKolifah; Muhammad Awal Satrio Nugroho (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to determine the role of motivation as a mediator of leadership dimensions on employe performance of PT. Netindo Solution. The population in this study are all employess of PT. Netindo Solution made with the criteria of being a permanent employee or more than one year from the criteria obtained a population of 400 employees spread from various division units. The sampling technique uses a purposive sampling technique of 80 respondents which will be taken 20% from 400 employees. The method of data collection uses a questionnaire method with a Likert scale. The data analysis technique used is path analysis. The results of the study show that Motivation (Y1) acts as a mediator between interpersonal roles (X1) of leaders and employee performance (Y2). This is evidenced by the indirect coefficient value of 0.308 greater than the direct coefficient value of 0.113. The results also prove that Motivation (Y1) acts as a mediator between the role of informational (X2) leaders and employee performance (Y2). This is evidenced by the indirect effect coefficient of 0.203 greater than the direct coefficient value of 0.220. Motivation (Y1) acts as a mediator between decisional roles (X3) of leaders and employee performance (Y2). This is evidenced by the indirect coefficient value of 0.216 greater than the direct coefficient value of 0.143. From the results of this study it can be concluded that through motivation, the role of dimensions will be more effective in improving the performance of employees of PT. Netindo Solution.